The research for flexible product family manufacturing based on real options - Maozhu Jin; Xiangguo Tian (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: The goal of this paper is to find the best production strategy for product portfolio, which means the largest value of the options. And finally, give a case and find the solution of the optimal production strategy for product portfolio. Design/methodology/approach: This article, based on the production with characteristics of a call option and 0-1 integer programming model, build new-product portfolio strategy, and through case demonstrate that traditional method underestimates the value of the product portfolio. Finding: According to market being volatility and uncertainty and the production can being delayed, firms can flexibly arrange the best time for products to manufacture. Use real options theory to analyze product decision and the best production timing decision. Find the total options value is higher than the traditional methods. Research limitations/implications: We are not applied to real option pricing theory in modular flexible production system. We just applied real option pricing theory to the product platform. The basic model need to improve. While the thinking of this paper provides some research ideas for flexible production systems based on real option in further research. Practical Implications: The introduction of the real option make the company can achieve dynamic planning and flexible management for production of product portfolio and get the better benefit. Originality/value: The central contribution of this paper is to introduce the option mechanism in the production timing for the product portfolio.
Keywords: 650; flexible product platform; product family; real option; binary pricing theory; 0-1 mathematical programming